1998
DOI: 10.1007/s002040050503
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of early acute lung injury in rodents exposed to phosgene

Abstract: Phosgene is a highly reactive oxidant gas used in the chemical industry. Phosgene can cause life-threatening pulmonary edema by reacting with peripheral lung compartment tissue components. Clinical evidence of edema is not usually apparent until well after the initial exposure. This study was designed to investigate early signs of acute lung injury in rodents within 45-60 min after the start of exposure. Male mice, rats, or guinea pigs were exposed to 87 mg/m3 (22 ppm) phosgene or filtered room air for 20 min … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
41
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(44 citation statements)
references
References 29 publications
3
41
0
Order By: Relevance
“…This is probably due to the rapid extracellular oxidation of GSH (Winterbourn et al, 2000). The increase of total GSH in BAL fluid, despite being reduced in lung tissues in a mouse model of lung damage caused by oxidative stress, is probably associated with alveolar cell rupture (Sciuto, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…This is probably due to the rapid extracellular oxidation of GSH (Winterbourn et al, 2000). The increase of total GSH in BAL fluid, despite being reduced in lung tissues in a mouse model of lung damage caused by oxidative stress, is probably associated with alveolar cell rupture (Sciuto, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Oxidized proteins accumulate with aging (33-35), after lung injury or toxic inhalation (36), and in various pathological states, including diabetes (37) and Alzheimer's disease (38). Oxidative modification and functional inactivation of proteins may occur by direct interaction with the oxidizing substance or indirectly through interaction with free radicals or reactive oxidation products, such as the aldehydic intermediates MDA (39) and 4-hydroxynonenal (40).…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6] ROS production systems from activated polymorphonuclear leukocytes (PMNs) and endothelial cells are considered to be two major pathways in acute lung injuries. 7) Extensive studies have demonstrated that sources for ROS in the lungs are reduced nicotinamide adenine dinucleotide phosphate (NADPH) oxidase (including the phagocytic cell oxidase and nonphagocyte oxidase in the vascular endothelial cells), xanthine dehydrogenase/xanthine oxidase (XDH/XO), and mitochondrial respiration.…”
mentioning
confidence: 99%
“…There is some evidence demonstrating that lipid peroxidation may contribute to oleic acidinduced lung injury. 21,22) The contributions of NADPH oxidase, XDH/XO, and effects of the antioxidant defense system have been reported in animal models of acute lung injuries, 2,6,9,11,23,24) but only a few papers demonstrated an involvement of the system in oleic acid-induced lung injury. 24) In addition, the characteristics of the ROS-generating pathway with oleic acid-induced lung injury are unclear.…”
mentioning
confidence: 99%